Optimalisasi Pendidikan Dini : Sosialisasi Ekonomi dan Pengenalan Uang Bagi Anak Usia Dini di Desa Telaga Jernih - Farah Aliyah Nafiza Sembiring; Uswah Hasanah (Lembaga Pengembangan Kinerja Dosen, 2024)
The Community Service Program (KKN) is a form of community service carried out by students as part of the Tri Dharma of Higher Education. The KKN activity carried out in Telaga Jernih Village, Langkat Regency, aims to improve financial literacy among early childhood. This program focuses on introducing basic economic concepts and money management through interactive activities involving children and the local community. One of the main activities in this program is making piggy banks from recycled materials, which not only aims to instill the habit of saving, but also increase environmental awareness. The method used in this activity is a qualitative approach with direct observation, interviews, and documentation. The results of this activity show a significant increase in children's understanding of the importance of saving and managing money wisely. Children who were previously not used to saving, began to show changes in behavior by setting aside their pocket money regularly. In addition, this program also has a positive impact on parents and the local community, who are beginning to realize the importance of financial education from an early age. However, the challenges faced in implementing this program are limited time and resources, which can affect the sustainability of saving habits among children after the program ends. Therefore, support from schools and parents is needed to ensure that the savings habits that have been taught can continue to develop. Overall, this program has made a significant contribution in forming awareness of the importance of financial literacy and money management among early childhood and the Telaga Jernih Village community.